Efficacy of ultrasound-guided microwave ablation combined with chemical ablation for uterine fibroid management - Zhao, Yu; Jiao, Tian-Pei; Zhang, Yu-Xiao; Wang, Na (Frontiers in Oncology, 2026)
BackgroundUterine fibroids are the most common benign tumors of the female reproductive tract and often cause menorrhagia, pelvic pain, and infertility. Ultrasound-guided microwave ablation (MWA) has gained recognition as a minimally invasive, uterus-preserving therapy; however, incomplete ablation may compromise long-term outcomes. This study aimed to evaluate the efficacy and safety of MWA combined with chemical ablation (CA) compared with MWA alone in patients with symptomatic fibroids.MethodsThis retrospective cohort study included women aged 18–55 years with imaging-confirmed uterine fibroids treated between January 2021 and December 2024. Patients were allocated to either the MWA+CA group (n=126) or the MWA group (n=108). Both groups underwent ultrasound-guided percutaneous ablation procedures. Treatment efficacy was assessed based on fibroid volume reduction, cure rates, and recurrence. Statistical analyses included independent-samples t-tests for continuous variables and chi-square tests for categorical variables.ResultsBoth treatment groups showed significant reductions in fibroid volume. The MWA+CA group experienced a more pronounced reduction, with a mean volume decrease from 33.64 ± 8.20 cm³ to 10.37 ± 2.25 cm³ (p < 0.001), compared to the MWA group, where the volume decreased from 32.36 ± 7.18 cm³ to 15.36 ± 3.27 cm³ (p < 0.001). The overall effective rate in the MWA+CA group was 98.4%, significantly higher than the 88.9% in the MWA group (p = 0.002). Recurrence rates were significantly lower in the MWA+CA group (1.6% vs. 8.3%, p = 0.015).ConclusionsUltrasound-guided MWA combined with CA is more effective in reducing fibroid volume and preventing recurrence compared to MWA alone. This combination offers a promising treatment option for symptomatic uterine fibroids, with no significant increase in adverse reactions. Larger, multicenter, prospective studies are needed to further validate these findings.